Construction of Multimodal Assessment Model of Consumption Potential in the Digital Economy Integrating Association Rule Mining Algorithm with D-ANP - ZHANG Tianjiao, ZHANG Zichao, HUANG Kun, ZHAO Youlin, LIN Yini (Nongye tushu qingbao xuebao, 2023)
[Purpose/Significance] Consumption is an important aspect of stimulating domestic demand. In the current development stage, the spatial and geographical distribution characteristics of our country indicate that domestic demand has great potential. However, the evaluation of consumption potential in the digital economy is a complex systematic project. Current research does not fully consider the correlation between evaluation indicators, and there are some problems such as low efficiency and too much reliance on the subjective experience of experts, which affect the scientific and reasonable evaluation results of consumption potential. [Method/Process] First of all, starting from each major work link that affects the consumption potential under the background of the digital economy, the preliminary evaluation index was determined through expert consultation and literature research and screening, and the primary evaluation index set of consumption potential under the background of the digital economy wasconstructed. Based on the consumption potential assessment data of Guangxi Zhongyan Industry Co., Ltd. from January to December 2021, the correlation and association rules among the assessment indicators were analyzed by using Apriori association rule mining algorithm, to streamline the assessment indicators and build an assessment index system of consumption potential in the context of the digital economy. The index system includes 11 secondary indicators and 19 tertiary indicators, such as user value, marketing communication effect, marketing ability, user participation, user influence, and channel effectiveness. Combining the influence relationship and influence degree between the quantitative evaluation indexes of DEMATEL and ANP, the weights of the evaluation indexes were calculated by the subjective and objective combination weighting method, to construct a multi-modal evaluation model of consumption potential in the digital economy. [Results/Conclusions] Taking six real dragon cigarette product marketing activities of Guangxi China Tobacco Industry Co., Ltd. from March to September 2021 as examples, the comprehensive scores of marketing activities in March, April, May, and June are 0.53, 0.52, 0.51 and 0.48, respectively, and the overall assessment result of consumption potential is "medium" level, among which the effect of marketing activities in August and September is better than that in March and June, and the comprehensive scores are 0.57 and 0.63, which are "medium to upper" level. On the whole, the impact of market influence ability, user value and marketing communication effect on the release of consumption potential decreases in turn. The analysis results are in good agreement with the actual situation, which verifies the feasibility and applicability of the multi-modal assessment model of consumption potential. In addition, due to the limited space, this paper only takes the tobacco industry as an example. In our future work, the specific index system can be adjusted according to the actual application needs.